PECULIARITIES OF PSYCHOLOGICAL COUNSELING OF WOMEN WITH REPRODUCTIVE DYSFUNCTION - N. V. Loseva; I. V. Yaroslavtseva (Acta Biomedica Scientifica, 2014)
The article reviews role and advantages of psychological counseling as the type of aid for women with reproductive dysfunction. We determined main peculiarities of psychological counseling of women: accounting anxiety level of primary customers and influence of emotional pain on somatic system; correction of emotional pain; negotiation of passive client's attitude; accounting time criterion; increase of effectiveness of psychological influence through the working with both husband and wife.